2005
DOI: 10.1097/00004850-200501000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Negative symptoms of schizophrenia are improved by the addition of paroxetine to neuroleptics: a double-blind placebo-controlled study

Abstract: Despite the availability of atypical antipsychotics, the treatment of negative symptoms in schizophrenia remains a challenge. This study was designed to confirm the positive effect observed in our pilot study with paroxetine as augmentation to antipsychotics in the treatment of negative symptoms in chronic schizophrenia. Twenty-nine patients with chronic schizophrenia, as defined by DSM-IV, who scored at least 20 points on the negative subscale of the Positive and Negative Syndrome Scale (PANSS) were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Some top candidates have been shown to improve negative symptoms in clinical studies, such as the H 2 antagonist ranitidine 39 and the alpha 2 receptor antagonist idazoxan 40 . The antidepressant paroxetine was also tested in a double-blind clinical trial and shown to be efficacious in ameliorating negative symptoms in schizophrenia 41 . There are other drug candidate with preliminary support by preclinical or clinical studies with diverse mechanisms, such as the serotonin and dopamine antagonist metitepine 42 , the Na-K-Cl cotransporter 1 inhibitor bumetanide 43 and the non-steroidal anti-inflammatory drug (NSAID) meclofenamic acid 44 .…”
Section: Drug Candidates Repositioned For Different Psychiatric Disormentioning
confidence: 99%
“…Some top candidates have been shown to improve negative symptoms in clinical studies, such as the H 2 antagonist ranitidine 39 and the alpha 2 receptor antagonist idazoxan 40 . The antidepressant paroxetine was also tested in a double-blind clinical trial and shown to be efficacious in ameliorating negative symptoms in schizophrenia 41 . There are other drug candidate with preliminary support by preclinical or clinical studies with diverse mechanisms, such as the serotonin and dopamine antagonist metitepine 42 , the Na-K-Cl cotransporter 1 inhibitor bumetanide 43 and the non-steroidal anti-inflammatory drug (NSAID) meclofenamic acid 44 .…”
Section: Drug Candidates Repositioned For Different Psychiatric Disormentioning
confidence: 99%
“…These residual symptoms might also be explained by a lesser efficacy of neuroleptics to control negative symptoms [41]. It is also possible that some symptoms such as reduced facial expression and energy might be extrapyramidal side effects of the medication rather than intrinsic negative symptoms [42].…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Clinical trials have provided evidence that the combined administration of an antipsychotic drug and an 'add-on' SSRI -such as fluoxetine, fluvoxamine, paroxetine or citalopram -can improve negative symptoms and some affective disorders associated with schizophrenia, without exacerbating extrapyramidal side effects, in patients in whom such problems have proved persistent and who have been, being unresponsive to antipsychotic monotherapy. [36][37][38][39][40][41] For example, the efficacy and safety of paroxetine augmentation has been demonstrated in small pilot studies 42 and a double-blind placebo-controlled study. 41 Fluvoxamine and fluoxetine have also shown some beneficial effects in placebo-controlled, double-blind studies, 36,38,43 in particular, fluvoxamine improved affective blunting.…”
Section: Efficacy Of Antidepressant Augmentation For Negative Symptomsmentioning
confidence: 99%
“…[36][37][38][39][40][41] For example, the efficacy and safety of paroxetine augmentation has been demonstrated in small pilot studies 42 and a double-blind placebo-controlled study. 41 Fluvoxamine and fluoxetine have also shown some beneficial effects in placebo-controlled, double-blind studies, 36,38,43 in particular, fluvoxamine improved affective blunting. Fluoxetine in combination with a depot antipsychotic caused an overall improvement in negative symptoms, 38 although it failed to do so in combination with clozapine.…”
Section: Efficacy Of Antidepressant Augmentation For Negative Symptomsmentioning
confidence: 99%
See 1 more Smart Citation